Does public service motivation really make a difference on the job satisfaction and turnover intentions of public employees? - Bright, Leonard (2008)
Many in public administration hypothesize that public service motivation (PSM) has a direct positive impact on the attitudes and behaviors of public employees. However, there are inconsistencies in the PSM literature that challenge this hypothesis. This study sought to find out whether person-organization (P-O) fit can provide a reason for these inconsistencies. Specifically, this study explored whether the relationships among PSM, job satisfaction, and the turnover intentions of public employees were mediated by P-O fit. Using a sample of 205 employees drawn from three public organizations in the states of Oregon, Indiana, and Kentucky, this study found that PSM had no significant to the job satisfaction and tturnover intentions of public employees when P-O fit was considered. The implications of this study and areas of future research are discussed. - Reproduced.
Keywords: Civil service; Job satisfaction; Motivation